Lectotypification of names of Neotropical species of Mucuna (Leguminosae: Papilionoideae: Phaseoleae). Issue 2 (27th December 2018) - Moura, Tânia M.; Tozzi, Ana Maria G.A.; Mansano, Vidal F.; Lewis, Gwilym P.
Abstract: Systematic studies of Neotropical species of Mucuna are relatively scarce. As a precursor to further taxonomic studies of this genus, we here propose lectotypes for seven New World taxa.